SOME PROBLEMS OF PHILOSOPHY METHODOLOGY IN THE CONTEXT OF COMPLEXITY - Doctor of Philosophy, Prof. M. N. Abdullaeva; Doctor of Philosophy, Prof. G. T. Makhmudova (Journals Park Publishing, 2024)
The article examines modern methodological problems of philosophy. The authors identify trends The rapidly changing contemporary world brings new issues, and tasks, the understanding of which requires new philosophical and methodological attitudes. At the same time, the authors analyse the developed and meaningful worldviews based on modern scientific data. According to the authors, a philosophical analysis of a rapidly changing, unstable world operates with such concepts as uncertainty, instability, complexity, nonlinearity, and openness, as well as various options for the future.
Keywords: system, uncertainty, instability, complexity, nonlinearity, openness, methodology, worldview.